Kepuasan Masyarakat Terhadap Daya Tarik Wisata Panorama Alam Pabangbon, Kabupaten Bogor, Provinsi Jawa Barat - Gantina, Devita; Rachman, Arief Faizal (Jurnal Ilmiah Pariwisata, 2020)
The development of tourism is increasingly interesting to study, given that the number of development of alternative tourist destinations and newly formed for domestic and foreign tourists who travel. Bogor Regency has a goal to improve the quality of tourist destinations. This study provides an overview of how an outdoor recreation attraction has an impact on local community satisfaction. The community receives and feels satisfaction as a host so that the hospitality of the community at a tourist destination can also give satisfaction to tourists. This study uses descriptive quantitative methods, carried out in cross-sectional way, data collection techniques by distributing questionnaires. Respondents are local people who live around Panorama Alam Pabangbon. Sampling using the Cluster sampling method Data analysis methods are validity and reliability tests, descriptive statistical analysis, using the help of SPSS 21 software for windows. The number of samples in this study amounted to 100 people. Data collection using a questionnaire that was tested for validity and reliability. The results of the study indicate that public satisfaction about the tourist attraction of Bukit Panorama Pabangbon is satisfactory with an average value of 143.78 in the range of scores 140 - <170 with a percentage of 50%.